Development of probiotic nanovesicles for oral delivery in inflammatory bowel disease (IBD) treatment - Lin, Xiang (Nanyang Technological University, 2024)
This study aimed to optimize the existing formulation of a bioink using sodium alginate for the 3D printing of extracellular vesicle (EV)-loaded beads, and to evaluate the therapeutic efficacy of probiotic-derived EVs in an in vivo inflammatory bowel disease (IBD) model. The shear-thinning behaviour of bioink is one important criteria to ensure both smooth extrusion and post-print structural integrity. Rheological characterization demonstrated that pure sodium alginate at a concentration of 4% demonstrated optimal shear-thinning properties, while the concentration of 2% had the best balance between printability and ease of preparation. The addition of methyl cellulose would enhance the shear-thinning behaviour, but with a more porous structure and weaker crosslinking efficiency. Thus, effectiveness of methyl cellulose as a strength- enhancing additive remains questionable and more studies need be done to on different composition, or new ingredients if possible. The characterization of 3D-printed beads showed that using a 20G nozzle and optimized extrusion parameters resulted in beads with larger volume and with consistent size and shape. Despite slight shape deformation passing through the feeding tube, in vitro release profile showed sustained EV release over a 24-hour period in deionised water, confirming successful encapsulation. In vivo studies using a dextran sodium sulfate (DSS)-induced colitis mouse model demonstrated the therapeutic potential of LGG-derived EVs. Mice treated with EVs exhibited milder symptoms of colitis inflammation, as evidenced lower weight loss, improved stool consistency, and less blood present in stool. Additionally, H&E staining confirmed better histological structure, and RT-PCR results showed that EVs suppressed the overexpression of proinflammatory gene IL-12 induced by DSS, which is a target pathway for IBD treatment. However, although encapsulating EVs in alginate allowed for targeted delivery, it showed lower efficacy compared to liquid EV administration. This may be due to challenges in oral administration and incomplete release of encapsulated EVs in the colon. These findings underscore the potential of LGG-derived EVs as a promising treatment for IBD and highlight the utility of 3D-printed bioink formulations in enhancing targeted EV delivery.